1978
DOI: 10.3168/jds.s0022-0302(78)83753-9
|View full text |Cite
|
Sign up to set email alerts
|

Complete Versus Selective Dry Cow Therapy for Mastitis Control

Abstract: Two hundred and thirty-two cows were assigned alternately to complete dry cow therapy (infusion in all quarters on the day of drying off) or selective therapy (infusion in all quarters if a history of mastitis, California Mastitis Test score of +2 or +3 in any quarter, or if cell counts from bucket milk samples as determined by the membrane filter-deoxyribonucleic acid procedure were above 500,000 cells/ml). A dry cow product containing 10(6) units of procaine penicillin G and 1 g of dihydrostreptomycin in a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
2
10

Year Published

1988
1988
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 19 publications
5
36
2
10
Order By: Relevance
“…In a meta-analysis of 5 studies, blanket DCT was compared with selective DCT and showed no significant difference in protection against new IMI in 3 studies when cow-level selection was practiced for drying off with antibiotics. This indicates no preventive effect of DCT in this approach (Rindsig et al, 1978;Browning et al, 1994;Williamson et al, 1995). However, these studies are hard to compare with our study because they were carried out over 20 yr ago in herds with different housing systems and with different production levels.…”
Section: Discussionmentioning
confidence: 41%
“…In a meta-analysis of 5 studies, blanket DCT was compared with selective DCT and showed no significant difference in protection against new IMI in 3 studies when cow-level selection was practiced for drying off with antibiotics. This indicates no preventive effect of DCT in this approach (Rindsig et al, 1978;Browning et al, 1994;Williamson et al, 1995). However, these studies are hard to compare with our study because they were carried out over 20 yr ago in herds with different housing systems and with different production levels.…”
Section: Discussionmentioning
confidence: 41%
“…Decisionmaking can be based on bacteriological culture (Robinson et al, 1988;Browning et al, 1990), SCC, and CM history (Rindsig et al, 1978;Torres et al, 2008;Rajala-Schultz et al, 2011), the California Mastitis Test (Rindsig et al, 1978;Bhutto et al, 2012), and N-acetylβ-d-glucosaminidase (Hassan et al, 1999), with different accuracies in identification of infected cows. When used in herds with low bulk milk SCC (<250,000 cells/ mL) to diagnose IMI in cows with a low SCC (<200,000 cells/mL) before drying off, a Petrifilm-based (3M, Minneapolis, MN) on-farm culture system for SDCT performed well, with a sensitivity of 85% and specificity of 73% (Cameron et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The successful outcome of an SDCT program depends on the accurate diagnosis of infection status at drying off so that DCT is applied appropriately and judiciously for the purpose of eliminating existing IMI. Furthermore, as prior studies have demonstrated that untreated quarters are at higher risk for the development of new IMI over the dry period, it is also important that a method to protect quarters against new IMI be in place, especially for cows not infused with DCT (Rindsig et al, 1978;Berry and Hillerton, 2002). According to the present study, when low-SCC cows were selectively treated with DCT at drying off based on results obtained using the Petrifilm on-farm culture system, no effect on milk production was noted in the subsequent lactation when compared with cows receiving BDCT.…”
Section: Test-day Milk Productionmentioning
confidence: 99%